Step * 1 1 2 1 of Lemma functor-is-isomorphism


1. [A] SmallCategory
2. [B] SmallCategory
3. Functor(A;B)@i
4. Functor(B;A)@i
5. functor-comp(f;g) 1 ∈ Functor(A;A)
6. functor-comp(g;f) 1 ∈ Functor(B;B)
7. ∀a:cat-ob(A). ((g (f a)) a ∈ cat-ob(A))
8. ∀b:cat-ob(B). ((f (g b)) b ∈ cat-ob(B))
9. ∀a1,a2:cat-ob(A). ∀x:cat-arrow(A) a1 a2.  ((g (f a1) (f a2) (f a1 a2 x)) x ∈ (cat-arrow(A) a1 a2))
⊢ ∀x,y:cat-ob(A).  Bij(cat-arrow(A) y;cat-arrow(B) (f x) (f y);f y)
BY
(Assert ∀b1,b2:cat-ob(B). ∀x:cat-arrow(B) b1 b2.  ((f (g b1) (g b2) (g b1 b2 x)) x ∈ (cat-arrow(B) b1 b2)) BY
         (Intros
          THEN StrengthenEquation 6
          THEN (ApFunToHypEquands `Z' ⌜b1 b2 x⌝ ⌜cat-arrow(B) b1 b2⌝ (-1)⋅
          THENM (RepUR ``functor-comp id_functor`` -1 THEN Eq)
          )
          THEN Fold `member` 0
          THEN InferEqualType
          THEN Auto
          THEN RepeatFor (D -1)
          THEN (RWO "-1" THENA Auto)
          THEN RepUR ``id_functor`` 0
          THEN Auto)) }

1
1. [A] SmallCategory
2. [B] SmallCategory
3. Functor(A;B)@i
4. Functor(B;A)@i
5. functor-comp(f;g) 1 ∈ Functor(A;A)
6. functor-comp(g;f) 1 ∈ Functor(B;B)
7. ∀a:cat-ob(A). ((g (f a)) a ∈ cat-ob(A))
8. ∀b:cat-ob(B). ((f (g b)) b ∈ cat-ob(B))
9. ∀a1,a2:cat-ob(A). ∀x:cat-arrow(A) a1 a2.  ((g (f a1) (f a2) (f a1 a2 x)) x ∈ (cat-arrow(A) a1 a2))
10. ∀b1,b2:cat-ob(B). ∀x:cat-arrow(B) b1 b2.  ((f (g b1) (g b2) (g b1 b2 x)) x ∈ (cat-arrow(B) b1 b2))
⊢ ∀x,y:cat-ob(A).  Bij(cat-arrow(A) y;cat-arrow(B) (f x) (f y);f y)


Latex:


Latex:

1.  [A]  :  SmallCategory
2.  [B]  :  SmallCategory
3.  f  :  Functor(A;B)@i
4.  g  :  Functor(B;A)@i
5.  functor-comp(f;g)  =  1
6.  functor-comp(g;f)  =  1
7.  \mforall{}a:cat-ob(A).  ((g  (f  a))  =  a)
8.  \mforall{}b:cat-ob(B).  ((f  (g  b))  =  b)
9.  \mforall{}a1,a2:cat-ob(A).  \mforall{}x:cat-arrow(A)  a1  a2.    ((g  (f  a1)  (f  a2)  (f  a1  a2  x))  =  x)
\mvdash{}  \mforall{}x,y:cat-ob(A).    Bij(cat-arrow(A)  x  y;cat-arrow(B)  (f  x)  (f  y);f  x  y)


By


Latex:
(Assert  \mforall{}b1,b2:cat-ob(B).  \mforall{}x:cat-arrow(B)  b1  b2.    ((f  (g  b1)  (g  b2)  (g  b1  b2  x))  =  x)  BY
              (Intros
                THEN  StrengthenEquation  6
                THEN  (ApFunToHypEquands  `Z'  \mkleeneopen{}Z  b1  b2  x\mkleeneclose{}  \mkleeneopen{}cat-arrow(B)  b1  b2\mkleeneclose{}  (-1)\mcdot{}
                THENM  (RepUR  ``functor-comp  id\_functor``  -1  THEN  Eq)
                )
                THEN  Fold  `member`  0
                THEN  InferEqualType
                THEN  Auto
                THEN  RepeatFor  2  (D  -1)
                THEN  (RWO  "-1"  0  THENA  Auto)
                THEN  RepUR  ``id\_functor``  0
                THEN  Auto))




Home Index